Menuju Parlemen Bikameral (Studi Konstitusional Perubahan Ketiga UUD 1945) - Dahlan Thaib (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The consequences of using these two chambers, it wipes out the district regulation/district representative and the composition of People's Consultative Assembly, so thatt here is no special position for the Indonesian National Armed Forces and The Indonesian Police Force at The People's Consultative Assembly. The Group Delegate and the representative of The Indonesian National Armed Forces and The Indonesian Police Force at The People's Consultative Assembly are deleted. It is taken because the apply of this people's representative system called bicameral as mentioned above namely Delegate and The Indonesian National Armed Forces/ The Indonesian Police Force can be manifestated through both Group two Legislative Board.